New species of Filaria (Nematoda: Filariidae) in the Lesser grison Galictis cuja (Molina) (Carnivora: Mustelidae) from northern Patagonia, Argentina and comments about the South American species of the genus - Bagnato, Estefanía (2022)
Filaria lorenzo n. sp. is described in the Lesser Grison, Galictis cuja from northern Patagonia, Argentina. The new species can be differentiated from the eight species of Filaria from the Old World by the shape of the sclerotized preesophageal ring. The four remaining species of the genus parasitize American Mephitidae and/or Mustelidae. Filaria carvalhoi from Brazil and F. texensis from USA lack a preesophageal ring, whereas F. taxideae from USA and F. conepati from Argentina share with our specimens a preesophageal ring mostly mushroom shaped. Our specimens differ from F. taxideae by lacking lateral alae, by a different ornamentation of the female tail and by the male lacking adcloacal papillae. The new species also differs from F. conepati by the shape of the preesophageal ring and by the shape of the eggs. The indirect examination of the types of F. conepati and F. carvalhoi, corroborated the existence of differences between these two species, allowing us to refute their synonymy, as proposed by some authors. Our results extend the taxonomy of Filaria to 13 species and comprise the first report of a filarioid nematode for an Argentinean mustelid, and the first report for Patagonia.